Soil Biodiversity Supports Agroecosystem Services Under Multiple Global Change Factors - Catalina Garzón‐Ladino; Guiyao Zhou; Daniel Revillini; Samuel Castejon; Yuanyuan Bao; Youzhi Feng; Manuel Delgado‐Baquerizo (Global Change Biology, 2026)
Cereals are the key staple foods supporting a growing population under global change. Soil biodiversity sustains ecosystem multifunctionality (EMF) that underpins food production and soil agroecosystem services. Yet, the capacity of soil biodiversity to support EMF in cereal fields under multiple global change factors (GCFs) remains virtually unknown. Here, we conducted a field mesocosm experiment involving wheat, four levels of soil biodiversity, and up to eight distinct GCFs (warming, drought, salinity, heavy metals, nitrogen addition, microplastics, pesticides, and alkalinization) to investigate the contributions of soil biodiversity in supporting EMF (e.g., crop productivity, nutrient cycling, plant symbionts, plant health and organic matter decomposition) under multiple GCFs. Our results reveal that soil biodiversity maintains positive effects on EMF under increasing levels of GCFs. Intermediate levels of multiple GCFs stimulated vegetative wheat biomass, likely due to compensatory responses, but often at the expense of other soil ecosystem functions such as organic matter decomposition or the prevalence of plant symbionts, highlighting the inherent trade‐offs under global change. These findings demonstrate that preserving soil biodiversity is essential to maintain agroecosystem functioning under multiple global change factors.